IDENTIFIKASI TANAMAN BERDASARKAN TIPE FOTOSINTESIS PADA BEBERAPA SPESIES ANGGOTA GENUS FICUS MELALUI PENGAMATAN ANATOMI DAUN - Wibawani, Alif Intan; Laily, Ainun Nikmati (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2015)
Photosynthesis is the process of carbohydrate synthesis of inorganic materials in plants pigmented with the help of sunlight energy. Based on the type of photosynthetic plants are divided into three kinds, namely C3, C4 and CAM. More adaptive C3 plants under conditions of high atmospheric CO2 content and do not have vascular sheath while the C4 plant more adaptive hot and dry areas, have a vascular sheath cells which are well developed and contain chloroplasts when observed anatomic structures. The purpose of this study was to identify plants by type of photosynthesis in Ficus callosa, F. elastica, F. benjamina, F. fistulosa, F. septica, F. rubiginosa and F. pisocarpa through leaf anatomical observations that cut transversely. The results showed that F. elastica and F. callosa have well-developed sheath cells surrounding the xylem and phloem, while F. benjamina, F. fistulosa, F. septica, F. rubiginosa and F. Pisocarpa are not